2020
DOI: 10.3390/cryst10100862
|View full text |Cite
|
Sign up to set email alerts
|

Electric Transport of Nodal Line Semimetals in Single-Component Molecular Conductors

Abstract: We examine an effect of acoustic phonon scattering on the electric conductivity of a single-component molecular conductor [Pd(dddt)2] (dddt = 5,6-dihydro-1,4-dithiin-2,3-dithiolate) with a half-filled band by applying the previous calculation in a two-dimensional model with Dirac cone [Phys. Rev. B. 98, 161205 (2018)], wherethe electric transport by the impurity scattering exhibits a noticeable interplay of the Dirac cone and the phonon scattering, resulting in maximum of the conductivity with increasing tempe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
(81 reference statements)
0
6
0
Order By: Relevance
“…Taking a moderate magnitude of the e-p coupling constant, the almost T independent conductivity in the 2D plane has been obtained. 35) Finally, we compare our result with that of experiment. Temperature dependence of resistance (corresponding to the inverse of the conductivity) under hydrostatic pressures shows nearly constant behavior at high temperatures and a minimum at low temperatures, while the minimum is invisible for uniaxial pressure.…”
Section: Summary and Discussionmentioning
confidence: 83%
“…Taking a moderate magnitude of the e-p coupling constant, the almost T independent conductivity in the 2D plane has been obtained. 35) Finally, we compare our result with that of experiment. Temperature dependence of resistance (corresponding to the inverse of the conductivity) under hydrostatic pressures shows nearly constant behavior at high temperatures and a minimum at low temperatures, while the minimum is invisible for uniaxial pressure.…”
Section: Summary and Discussionmentioning
confidence: 83%
“…However, the donors with cycloalkane substituents can adjust the proportions of the inter-and intra-dimer interactions through the S•••S contacts in their radical cation crystals by modification of the cycloalkane moieties, and allow for the realization of various cation radical crystals with unique donor arrangements by introducing linear, tetrahedral, and octahedral anions. Moreover, neutral crystals are potential candidates for new single-component molecular conductors [58][59][60][61][62][63].…”
Section: Molecular Orbitals and Energy Band Calculations Of 9 And 10mentioning
confidence: 99%
“…A cation radical crystal, [Ni(dddt) 2 ] 3 (AuBr 2 ) 2 , is the first metal based on the donor-type metal-dithiolene complexes exhibiting metallic behavior down to at least 1.3 K [57]. Recently, Kato et al reported a single-component molecular Dirac electron system based on Pd(dddt) 2 that exhibits temperature-independent resistivity under high hydrostatic pressures [58][59][60][61][62][63]. The conducting and magnetic properties exhibited by the molecular crystals based on the dithiolene complexes are significantly dependent on the molecular arrangements of the metal-dithiolene complexes and organic molecular conductors.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the Dirac electron systems (DESs), or more generally topological materials (TMs), have been paid increasing attention [1][2][3][4][5][6][7][8]. In organic or molecular materials, the charge-transfer (CT) complexes/salts containing DESs called zero-gap conductors (ZGCs) have been intensively studied for nearly two decades [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. This is not only because of their unique physical properties, but also because of their advantage for research on basic electronic properties and the mechanism of production of DESs owing to the well-defined structures and stoichiometries.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the wide variety of organic ZGCs based on finely controllable syntheses add an advantage for systematic studies. Since the discovery of the ZGC in organic compounds, α-ET 2 I 3 under high pressure (p > 12-15 kbar) (ET = bis(ethylenedithio)tetrathiafulvalene, Figure 1) [9], many kinds of molecular crystalline materials have also been reported to exhibit electronic properties and band structures characteristic to the ZGCs [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. In this way, our understanding of organic ZGCs has made substantial progress over the last 10-15 years, regarding band structures and electrical and magnetic properties.…”
Section: Introductionmentioning
confidence: 99%